Towards Acacia seyal protocol in Sudan: Preliminary study pertinent to colour identification and physiochemical properties. (July 2018) - Sara, S. Awad; Ali, A. Rabah; Hassan, I. Ali; Tarig, E. Mahmoud; Hassan, A. Mudawi
Abstract: Despite the significant contribution of A. seyal to the exports portfolio of Sudan, farmers have slightly poor knowledge regarding post-harvest cultural practices in terms of proper methods of gum drying, storage conditions and gum stacking which might significantly be resulted in colour deterioration and inferior quality. Nevertheless, the current preliminary investigation is intended to study colour identification and physiochemical properties of A. seyal gums from samples obtained viafour exporting companies in Sudan and produced in three different geographical areas namely Buram, Hejleij and Deain . Each sample was graded visually into three colours: light, pale and dark and based on further chemical analysis to the colour within the samples and across the production areas significant variation was obtained as the colour is ranging from 16.73 to 44.53 within the different graded samples and across the production areas. The results show that each sample is graded into three different colour scale refereed to light, pale and dark. The physiochemical properties within the tested samples and across the production areas showed no significant differences between all parameters including moisture content, ash content and pH. The specific optical rotation varies from + 40 to + 60 within the samples and across the different production areas. However, both minimum and maximum values of specific optical rotation were obtained from Hejleij production area and representing light and dark colour, respectively. Highlights: Samples of Acacia seyal (Talha) obtained from different production areas of Sudan showed visually variations in colours: light, pale and dark further chemical analysis confirmed such results. Significant variation was obtained as the colour within the different graded samples and across the production areas. The physiochemical properties within the tested samples and across the production areas showed no significant differences between all parameters. Colour intensity is positively correlated with specific optical rotation.